Hahnemann's principles and anthropology of transcendent philosophy: An observation in the light of Islamic sources - Mohd. Nor, Hanapi (2012)
Ever since human being lives within space and time, body and soul are inseparable twin. This is an everlasting rule that ought to constantly reminded us, while dealing with human nature as well as with progress and civilization, to look for the physical, psycho-physical and spiritual, as well their inter-relationship; hence pinpointing the significance of the transcendent reality. However, philosophers through the ages have been perplexed by the relationship between the material aspect of man, his body, and the immaterial or spiritual aspect which inhabit it. Friedrich Samuel Hahnemann (1755-1845 C.E) was brought up in the rationalistic thinking of the enlightenment. Then, "he advanced beyond this to spiritualism." Hahnemann began his scientific work with "emphasis on scientific exactitude and empiric certainty as the starting point of his therapeutic reform," and later became "a strong opponent of materialism." He was born in Meissen, Saxony on April 10, 1755, Hahnemann showed early proficiency at languages, and by the age of twenty had mastered English, French, Italian, Greek and Latin, and was making a living as a translator and teacher of languages. He later became proficient in Arabic, Syriac, Chaldaic and Hebrew. He lived) in the 19th century. The period in which the theory evolution was established. The deeper study of Hahnemann, however, bring us to the roots of his principles . The roots lie in Unitarianism. In the European history, proto-Unitarian and Unitarian arguments over religion in the 18th and early 19th centuries raise the matter of Islam (or Mohammadism, as it was typically called). The early Unitarians of Europe were willing to point to Islam as evidence for the correctness of their viewpoint. However, under the pretext of modern philosophy and science, almost all modern disciplines of knowledge tend to ignore Islamic factors as they ignore the subtle and un-observable part of human nature, by mainly focusing on the observable and quantifiable reality. Modern philosophy that fathered modern science, which in the 17th and 18th centuries went by the names of rationalism, existentialism, humanism, empiricism etc., were devoid of transcendental dimensions. This study seeks to retrace human nature and transcending the vision of humanity, by identifying, describing and analyzing the Hahnemann’s principles and their relevance to anthropology of transcendent philosophy. Using the qualitative data from Hahnemann’s works with special reference to his Organon we found that Hahnemann’s principles are, unquestionably, a philosophical system in its own right.The primary goal of his philosophy, however is not solely speculative, indeed it is a medical philosophy written in brief aphoristic style, aimed more of guidelines at curing suffering human beings, rather than winning adherents to its speculative creed. The main concern of Hahnemann with regard to his medical philosophy is actually the question of suffering human well-being.